NOMINALISATION IN LEGAL LANGUAGE - DOLATA-ZARÓD, Anna (Comparative Legilinguistics, 2011)
Legal discourse is a combination of history, tradition, rules and forms. There are specific syntactic structures and other features typical of legal discourse and having mortho-syntactic features affecting the semantic content of messages. The rules of construction (or in other words interpretation) of legal texts are often unclear and ambiguous for both lay persons and lawyers. The author focuses her attention on nominalisations in the langauge of statutory instruments. The analysis aims at showing typical features of nominalised structures in statutory instruments and the purpose of applying them.